Emerging Role of Exosomal Long Non-coding RNAs in Spaceflight-Associated Risks in Astronauts - Bisserier, Malik; Saffran, Nathaniel; Brojakowska, Agnieszka; Sebastian, Aimy; Evans, Angela Clare; Coleman, Matthew A.; Walsh, Kenneth; Mills, Paul J.; Garikipati, Venkata Naga Srikanth; Arakelyan, Arsen; Hadri, Lahouaria; Goukassian, David A. (Frontiers in Genetics, 2022)
During spaceflight, astronauts are exposed to multiple unique environmental factors, particularly microgravity and ionizing radiation, that can cause a range of harmful health consequences. Over the past decades, increasing evidence demonstrates that the space environment can induce changes in gene expression and RNA processing. Long non-coding RNA (lncRNA) represent an emerging area of focus in molecular biology as they modulate chromatin structure and function, the transcription of neighboring genes, and affect RNA splicing, stability, and translation. They have been implicated in cancer development and associated with diverse cardiovascular conditions and associated risk factors. However, their role on astronauts' health after spaceflight remains poorly understood. In this perspective article, we provide new insights into the potential role of exosomal lncRNA after spaceflight. We analyzed the transcriptional profile of exosomes isolated from peripheral blood plasma of three astronauts who flew on various Shuttle missions between 1998-2001 by RNA-sequencing. Computational analysis of the transcriptome of these exosomes identified 27 differentially expressed lncRNAs with a Log2 fold change, with molecular, cellular, and clinical implications.